Poro-mechanical model of strain hysteresis due to cyclic water freezing in partially saturated porous media. (1st December 2020) - Gawin, Dariusz; Pesavento, Francesco; Koniorczyk, Marcin; Schrefler, Bernhard A.
Highlights: Mathematical model of freezing–thawing processes in moist porous media is presented. Water – ice phase transition is modelled by means of a non-equilibrium approach. Effects of hysteresis, water supercooling, cyclic freezing strains are considered. Numerical solution of the model and results of sensitivity analysis are presented. Freezing strains are modelled with effective stresses and experimentally validated. Abstract: The paper presents a novel mathematical model of coupled hygro-thermo-mechanical processes in a porous material, partially saturated with liquid water and exposed to temperatures below the freezing point of pore water. Water – ice phase change is modelled by means of a non-equilibrium approach considering both water supercooling and a hysteresis of ice content during freezing and thawing of moist porous materials. The hysteresis results in different crystallization pressure and material strains during freezing and thawing processes at a given temperature. The latter effect is modelled by means of the effective stress principle, considering crystallization pressure of ice in the material pores. Methods used for discretization of the model equations and their numerical solution are described. The model is applied for solving the numerical example dealing with laboratory Dynamic Mechanical Analysis test of two different cement mortars saturated with water and exposed to temperatures below the freezing point of water (down to −15 °C) where hysteresis of strains was observed. The results are used for experimental validation of the proposed model. Then, for a 1-D case concerning water freezing-thawing of a wall, the effects on the simulation results of the phase-change model parameters, of the material hygro-thermal state, of the supercooling phenomenon and finally of the rate of temperature variation, are analyzed and discussed.